Challenges to Understanding and Compliance Among Surgical Patients in Low-Income Urban Teaching Hospitals. Issue 5 (May 2021) - Burgoon, Montgomry L.; Miller, Parker A.; Hoover-Hankerson, Bryson; Strand, Nicolle; Ross, Howard
Financial and educational barriers significantly impact low socioeconomic status racial and ethnic minority groups in their pursuit of health care, though less is known about the interplay of these factors in the pursuit of surgical care. This study was designed to uncover the challenges to patient understanding and compliance with pre- and postsurgical clinical advice in low-income urban environments. The data for this study were collected in spoken survey with eighty patients in 9 surgery clinics at Temple University Hospital in Philadelphia. Survey responses were coded into various groups until categories emerged. Relationships among categories were identified to generate themes and subthemes. Key facilitators of patient understanding and compliance were physician likeability and communication. Eighty (100%) patients reported that the physician always treated them with respect, which was important in their interpretation of their experience with the physician. Eighteen (23%) patients identified a language other than English as their primary language and 57 (71%) patients completed high school or less schooling, which likely influenced their communication with the physician. Eighty (100%) patients expressed that the physician always explained things in a way they could understand, focusing on clarity and thoroughness. Challenges to patient understanding and compliance were finances and social resources. Patients noted difficulty paying for medical care and a lack of support at home. Agency could facilitate use of surgical care while a lack thereof could challenge motivation. Ultimately, these themes showed how patients in this environment interact with surgical care.